Los aportes de la jurisprudencia al desarrollo del derecho internacional - Salas, Graciela R.; Drnas de Clément, Zlata; Pintore, Eduardo José; Galván, Susana; Pagliari, Arturo; Sartori, Marta Susana; García Montaño, Diego; Rodríguez de Taborda, María Cristina; Rey Caro, Ernesto J.; Sommer, Christian G.; Sticca, María Alejandra; García Elorrio, Magdalena; et al. (Academia Nacional de Derecho y Ciencias Sociales de Córdoba, 2022)
Fil: Salas, Graciela R. Academia Nacional de Derecho y Ciencias Sociales de Córdoba; Argentina.